Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 66554 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Mus musculus Linnaeus, 1758", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 66554 records from 151 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000256-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences